2015
DOI: 10.3390/molecules201017976
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Phenolic Composition, Antioxidant, Wound Healing and Cytotoxic Activities of Selected Achillea L. Species Growing in Turkey

Abstract: Turkey is one of the most important centers of diversity for the genus Achillea L. in the world. Keeping in mind the immense medicinal importance of phenols, in this study, three species growing in Turkey, A. coarctata Poir. (AC), A. kotschyi Boiss. subsp. kotschyi (AK) and A. lycaonica Boiss. & Heldr. (AL) were evaluated for their phenolic compositions, total phenolic contents (TPC), antioxidant properties, wound healing potencies on NIH-3T3 fibroblasts and cytotoxic effects on MCF-7 human breast cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 55 publications
5
71
0
4
Order By: Relevance
“…Phenolics (flavonoids and phenolic acids) have been reported for their redox potential, which allows them to chip in significantly as oxygen quenchers and reducing agents and in some cases even metal chelators (Pattanayaka and Sunita, 2008) imparting them potential in tackling inflammation (Sengar et al, 2015) and thereby wound healing (Akkol et al, 2012). Moreover, phenolic compounds have the ability to facilitate wound healing at different stages of wound healing either by stimulating collagen synthesis, cell proliferation and angiogenic effect (Agar et al, 2015). Chlorogenic acid quantified in the present study is a phenolic acid representing the class of hydroxycinnamic acid polyphenolic compounds and is a dimer of quinic acid and caffeic acid connected with an ester bond (Sato et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Phenolics (flavonoids and phenolic acids) have been reported for their redox potential, which allows them to chip in significantly as oxygen quenchers and reducing agents and in some cases even metal chelators (Pattanayaka and Sunita, 2008) imparting them potential in tackling inflammation (Sengar et al, 2015) and thereby wound healing (Akkol et al, 2012). Moreover, phenolic compounds have the ability to facilitate wound healing at different stages of wound healing either by stimulating collagen synthesis, cell proliferation and angiogenic effect (Agar et al, 2015). Chlorogenic acid quantified in the present study is a phenolic acid representing the class of hydroxycinnamic acid polyphenolic compounds and is a dimer of quinic acid and caffeic acid connected with an ester bond (Sato et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…These compounds contribute healing process at different stages by stimulating collagen synthesis and cellular proliferation. The present study also included quantification of chlorogenic acid, a natural antioxidant reported for its diabetic wound healing, wound healing, antimicrobial, anti‐inflammatory and antimutagenic, properties . The diabetic wound healing potential of chlorogenic acid was attributed to its enhanced collagen deposition, decreased malondialdehyde/nitric oxide levels, elevated reduced‐glutathione, and restoration of antioxidants such as SOD and CAT .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they have been pointed out as potent remedies to address some human disorders including haemorrhoid (Jaric et al, 2007) and gastrointestinal (Bibi et al, 2015;Martkoplishvili and Kvavadze, 2015) disturbances. They can also be utilized as effective factors in wound healing (Agar et al, 2015).…”
Section: Historical Traditional and Ethnomedicinal Uses Of The Achilmentioning
confidence: 99%
“…fumigatus (Bezic et al, 2003;Bekhechi et al, 2011;Falconieri et al, 2011), A. niger (Bezic et al, 2003;Ristic et al, 2004;Stojanovic et al, 2005;Falconieri et al, 2011), C. albicans (Barel et al, 1991;Magiatis et al, 2002;Unlu et al, 2002;Bezic et al, 2003;Candan et al, 2003;Sokmen et al, 2003;El-Shazly et al, 2004;Sokmen et al, 2004;Stojanovic et al, 2005;Tuberoso et al, 2005;Iscan et al, 2006;Bader et al, 2007;Karamenderes et al, 2007;Maggi et al, 2009;Turkoglu et al, 2010;Falconieri et al, 2011;Kucukbay et al, 2011;Radulovic et al, 2012;Albayrak, 2013;Kazemi and Rostami, 2015;Turkmenoglu et al, 2015;Fahed et al, 2016), C. glabrata (Magiatis et al, 2002;Al-Snafi, 2013), C. krusei (Candan et al, 2003;Sokmen et al, 2003;Falconieri et al, 2011;Turkmenoglu et al, 2015), C. herbarum (Bekhechi et al, 2011), C. kefyr (Ghasemi et al, 2008), C. krusei (Candan et al, 2003;Sokmen et al, 2003;Falconieri et al, 2011;Turkmeno...…”
Section: Antifungal Activitiesmentioning
confidence: 99%
See 1 more Smart Citation